Silk Polymers and Nanoparticles: A Powerful Combination for the Design of Versatile Biomaterials - Belda Marín, Cristina; Fitzpatrick, Vincent; Kaplan, David L.; Landoulsi, Jessem; Guénin, Erwann; Egles, Christophe (Frontiers in Chemistry, 2020)
Silk fibroin (SF) is a natural protein largely used in the textile industry but also in biomedicine, catalysis and other materials applications. SF is biocompatible, biodegradable and possesses high tensile strength. Moreover, it is a versatile compound that can be formed into different materials at the macro, micro- and nano-scales, such as nanofibers, nanoparticles, hydrogels, microspheres, and other formats. Silk can be further integrated into emerging and promising additive manufacturing techniques like bioprinting, stereolithography or digital light processing 3D printing. As such, the development of methodologies for the functionalization of silk materials provide added value. Inorganic nanoparticles (INPs) have interesting and unexpected properties differing from bulk materials. These properties include better catalysis efficiency (better surface/volume ratio and consequently decreased quantify of catalyst), antibacterial activity, fluorescence properties, and UV-radiation protection or superparamagnetic behavior depending on the metal used. Given the promising results and performance of INPs, their use in many different procedures has been growing. Therefore, combining the useful properties of silk fibroin materials with those from INPs is increasingly relevant in many applications. Two main methodologies have been used in the literature to form silk-based bionanocomposites: in situ synthesis of INPs in silk materials, or the addition of preformed INPs to silk materials. This work presents an overview of current silk nanocomposites developed by these two main methodologies. An evaluation of overall INP characteristics and their distribution within the material is presented for each approach. Finally, an outlook is provided about the potential applications of these resultant nanocomposite materials.